Ibrutinib for mantle cell lymphoma at first relapse: a United Kingdom real‐world analysis of outcomes in 211 patients. (23rd February 2021) - McCulloch, Rory; Lewis, David; Crosbie, Nicola; Eyre, Toby A.; Bolam, Simon; Arasaretnam, Anita; Creasey, Thomas; Goradia, Harshita; McMillan, Annabel; Dawi, Safia; Harrison, Samuel; Miles, Oliver; et al.
Summary: Ibrutinib is an established treatment for relapsed/refractory (R/R) mantle cell lymphoma (MCL) and clinical trial data supports use at second line compared to later relapse. We aimed to investigate outcomes and tolerability for ibrutinib when given second line in a real‐world setting. Our multicentre retrospective analysis included 211 R/R MCL patients, median age 73 years, receiving ibrutinib second‐line within the United Kingdom's National Health Service. Overall response to ibrutinib was 69% (complete response 27%). The median progression‐free survival (PFS) was 17·8 months (95% CI 13·1–22·2) and median overall survival (OS) 23·9 months (95% CI 15·0–32·8). Drug‐related adverse event led to dose reduction in 10% of patients and discontinuation in 5%. In patients with progressive disease, accounting for 100 of 152 patients stopping ibrutinib, 43% received further systemic therapy. Post‐ibrutinib rituximab, bendamustine and cytarabine (R‐BAC) showed a trend toward improved survival compared to alternative systemic treatments (post‐ibrutinib median OS 14·0 months, 95% CI 8·1–19·8, vs. 3·6 months, 95% CI 2·6–4·5, P = 0·06). Our study confirms the clinical benefit and good tolerability of ibrutinib at first relapse in a real‐world population. Patients progressing on ibrutinib had limited survival but outcomes with R‐BAC in select patients were promising.